First successful reduction of clinical allergenicity of food by genetic modification: Mal d 1‐silenced apples cause fewer allergy symptoms than the wild‐type cultivar. Issue 11 (24th July 2015) - Dubois, A. E. J.; Pagliarani, G.; Brouwer, R. M.; Kollen, B. J.; Dragsted, L. O.; Eriksen, F. D.; Callesen, O.; Gilissen, L. J. W. J.; Krens, F. A.; Visser, R. G. F.; Smulders, M. J. M.; Vlieg‐Boerstra, B. J.; et al.
Abstract Background Genetic modification of allergenic foods such as apple has the potential to reduce their clinical allergenicity, but this has never been studied by oral challenges in allergic individuals. Methods We performed oral food challenges in 21 apple‐allergic individuals with Elstar apples which had undergone gene silencing of the major allergen of apple, Mal d 1, by RNA interference. Downregulation of Mal d 1 gene expression in the apples was verified by qRT‐PCR. Clinical responses to the genetically modified apples were compared to those seen with the wild‐type Elstar using a visual analogue scale (VAS). Results Gene silencing produced two genetically modified apple lines expressing Mal d 1.02 and other Mal d 1 gene mRNA levels which were extensively downregulated, that is only 0.1–16.4% (e‐DR1) and 0.2–9.9% (e‐DR2) of those of the wild‐type Elstar, respectively. Challenges with these downregulated apple lines produced significantly less intense maximal symptoms to the first dose (Vmax1) than with Elstar (Vmax1 Elstar 3.0 mm vs 0.0 mm for e‐DR1, P = 0.017 and 0.0 mm for e‐DR2, P = 0.043), as well as significantly less intense mean symptoms per dose (meanV/d) than with Elstar (meanV/d Elstar 2.2 mm vs 0.2 mm for e‐DR1, P = 0.017 and 0.0 mm for e‐DR2, P = 0.043). Only one subject (5%) remained symptom‐free when challenged with the Elstar apple, whereas 43% did so with e‐DR1 and 63% with e‐DR2. Conclusion These data show that mRNA silencing of Mal d 1 results in a marked reduction of Mal d 1 gene expression in the fruit and reduction of symptoms when these apples are ingested by allergic subjects. Approximately half of the subjects developed no symptoms whatsoever, and virtually all subjects wished to consume the apple again in the future.